Književne študije: o vlogi ženske v slovenski književnosti, o sodobni prozi in o slovenski književnosti v Avstriji - Borovnik, Silvija (University of Maribor Press, 2012)
Literary Studies: about the Role of a Woman in Slovene Literature, on Contemporary Prose and on Slovene Literature in Austria. This monograph reveals the fundamental research interests of the author prof. dr. Silvia Borovnik. These are prose and partly poetry of 20th-century Slovenian writers, prose of contemporary Slovene writers, problems of Slovene literature in Austria, and problems of literary translation. In all of these areas, the proposed monograph brings new and interesting results for the literary. In the first part, the author deals with the work of Slovenian writers, which is still unknown and in literary science, analyzes the novels and short prose of recent authors, emphasizing the thematic and linguistic and stylistic innovations that their literature translates into contemporary Slovene prose. Borovnikova also writes about the work of Slovene women writers in Austria, treating some contemporary Slovene women writers from the point of view of their intercultural connections, thus pointing to a particular phenomenon of bilingualism and interculturalism in literature that the past did not know. He further discusses the bilingualism of Slovene literature in Austria and emphasizes that it is an expression of a dual identity and that Slovenian as a language of literature is sometimes almost lost. On the whole, Literary Studies brings many interesting lessons and provides a good basis for further research in the field of contemporary Slovenian literary history. The author uses appropriate literary and historical terminology based on the works of prominent Slovenian and foreign scholars, and her language is cultivated and communicative, so that the book is also suitable for a wider range of readers interested in Slovene literature.